2017
DOI: 10.1038/s41598-017-03309-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute administration of catalase targeted to ICAM-1 attenuates neuropathology in experimental traumatic brain injury

Abstract: Traumatic brain injury (TBI) contributes to one third of injury related deaths in the US. Treatment strategies for TBI are supportive, and the pathophysiology is not fully understood. Secondary mechanisms of injury in TBI, such as oxidative stress and inflammation, are points at which intervention may reduce neuropathology. Evidence suggests that reactive oxygen species (ROS) propagate blood-brain barrier (BBB) hyperpermeability and inflammation following TBI. We hypothesized that targeted detoxification of RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 81 publications
3
51
0
1
Order By: Relevance
“…Given this increasing prevalence of endovascular intervention, IA administration of drug carriers has a potential role in the treatment of a variety of CNS disorders 8,26 . Acute and chronic central nervous diseases, including stroke 27 , meningitis 19 , traumatic brain injury 28 , Alzheimer's diseases 15 and multiple sclerosis 29 are all accompanied by neurovascular inflammation. Inflammatory mediators and abnormal hemodynamics induce or augment surface exposure of endothelial cellular adhesion molecules such as ICAM-1, VCAM-1, ALCAM, P-selectin, and Eselectin, among others 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Given this increasing prevalence of endovascular intervention, IA administration of drug carriers has a potential role in the treatment of a variety of CNS disorders 8,26 . Acute and chronic central nervous diseases, including stroke 27 , meningitis 19 , traumatic brain injury 28 , Alzheimer's diseases 15 and multiple sclerosis 29 are all accompanied by neurovascular inflammation. Inflammatory mediators and abnormal hemodynamics induce or augment surface exposure of endothelial cellular adhesion molecules such as ICAM-1, VCAM-1, ALCAM, P-selectin, and Eselectin, among others 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The BBB breakdown restoration via quinpirole might be due to reduction of neuroinflammation and active gliosis in the brain. The previous study also observed that brain injury is critically associated with deregulated tight junction proteins [54]. Due to mark tissue disruption after brain injury [41], the Nissl stained cortical section of the injured brains indicated that there was a significant increase in lesion volume while quinpirole treatment significantly restored the lesion volume suggesting that quinpirole is important to repair the brain after injury and restore the tight junction proteins to inhibit cytokines infiltration and other blood-born biochemical agents.…”
Section: Discussionmentioning
confidence: 84%
“…It is well known that edema formation, increased oxidative stress, calcium influx, excitotoxicity, inflammation and cell death or apoptosis contribute to the process of secondary injury ( Werner and Engelhard, 2007 ; Lutton et al, 2017 ). Brain edema exacerbation is a major and severe pathophysiological change induced by TBI ( Lutton et al, 2017 ). In our study, we found that Andro reduced TBI-induced brain edema, moreover, Andro decreased the expression of albumin after injury, indicating that Andro rehabilitate the BBB integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary brain injury is a complicated cellular processes and biochemical cascades which occur in minutes and last for days following the traumatic events, resulting in exacerbated damage, progressive neurodegeneration and cell death ( Kabadi and Faden, 2014 ). The mechanism of TBI-induced secondary injury includes glutamate excitotoxicity ( Hyder et al, 2007 ), oxidative stress ( Zhang et al, 2018 ), blood-brain barrier (BBB) disruption ( Lutton et al, 2017 ), neuroinflammation and mitochondrial dysfunction ( Lozano et al, 2015 ). It is well known that neuroinflammation occurs in both primary and secondary injury following TBI, as well as in other neurodegenerative diseases ( Eikelenboom et al, 2010 ; Perry et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%